Availability of Palm Oil Biodiesel in Indonesia and Its Effect on Diesel Engine: A Review - W Saputro; W D Lestari; L Edahwati; R D Issafira; A K Faizin; N Adyono; T P Sari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
Palm oil is one of the base ingredient that can be used in making of biodiesel which is an alternative fuel to replace diesel fuel. The ability of palm oil as biodiesel should be balanced with the quantity of palm oil as well as the level of biodiesel production capability. In this paper, authors try to analyze about palm oil as biodiesel starting from number of palm plantations up to the level of biodiesel production capability from palm oil. The analysis conducted in the first part of this paper can be used as a reference that shows the level of availability of the palm oil which can be processed into biodiesel as an alternative fuel in the future. In the next part, the authors tried to analyze the impact of biodiesel made from palm oil starting from engine performance, exhaust gas emissions, rate of wear, quality of lubricant, and deposit formed. It was is done in order to find out the advantages and disadvantages that occur from biodiesel so that it can be used as a reference or consideration in the use of biodiesel-fueled palm oil.